Peripheral nerve localization by frequency-based electrical stimulation - Dilok Puanhvuan (2018)
During surgery, the nervous system is at risk if surgeon could not localize nerve's location. In case of tumor blocked, the surgeon can completely not visualize the nerve due to the tumor. Hence, nerve localization is very important during to operation. Generally, the neurophysiologic intra-operative monitoring (NIOM) has alarming feature, when the surgeon irritated the nerve, they could pre-localize the nerve. However, this alarming is quite sensitive since it sometime alarms even when the surgeon hints other area expected the nerve. This would makes the surgeon qualitative evaluates location of the nerve. This study proposed the new modality of nerve localization. The nature of compound muscle action potential (CMAP) was used in this study. Given a frequency-based electrical stimulation to a targeted area, the CMAP would response if and only if the stimulating electrode was placed directly to the nerve. The results from preliminary study in animal revealed that applying the stimulation at 30Hz and 0.3Volt with 1.5 millimeters width of a bipolar electrode gave highest CMAP detection accuracy (97.5%). © Springer-Verlag 2013.